The future of the banking system under the dominance and development of the cryptocurrency industry: empirical evidence from cointegration analysis - Othman, Anwar Hasan Abdullah; Syed Jaafar Alhabshi, Syed Musa; Haron, Razali; Mohd Noor, Azman (Institutional Investor, Inc., 2019)
Bank stability and trust levels have been seriously affected by the 2007–2008 Global Financial Crisis, which led to the identification of a range of policies based on past experience intended to overcome the consequences of the crisis. The idea of cryptocurrency was introduced to handle the mistrust of financial intermediaries that led to the liquidity crisis. This study investigates whether the new cryptocurrencies have been able to perform the functions of financial intermediaries and offer the confidence level required by bank depositors, examining their long-run effect on banks’ deposit mobilization. The study applies a cointegration test analysis with a vector error correction model to examine this relationship. Overall results indicate that in the countries studied increases in the market capitalization of the cryptocurrency industry have a significant negative impact on banks’ deposit variability, while decreases have a positive impact, with a long-run equilibrium relationship. The outcomes of the study suggest that in order to regain the trust of depositors and avoid the effects of the cryptocurrency industry, banks should be encouraged to invest directly in cryptocurrency or should consider cryptocurrencies as an alternative investment asset for their portfolio investment diversification strategies during bullish market conditions and avoid them during bearish market conditions. Also, banks can incorporate blockchain technology into their operation system and compete with the cryptocurrency industry side by side in the financial market. If neither of these options is taken, however, the banking system may not be able to compete and sustain in the long term using the current operational model. The outcomes of this study can be used as policy guidance by central banks and the banking industry for the betterment of the industry.